THE CORRELATION OF LOVE BASED CURRICULUM AND DEEP LEARNING APPROACH TOWARD LEARNING OUTCOMES OF 2ND GRADE STUDENTS IN MATHEMATICS AT MIN 2 JEMBER - Frida Nur Izza Putri; Khurin 'In Ratnasari (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2026)
This study examines the influence of the Love-Based Curriculum and the deep learning approach on the mathematics learning outcomes of lower-grade students in Madrasah Ibtidaiyah, focusing on cognitive, affective, and psychomotor domains. The study aims to determine the extent to which the integration of these two approaches relates to students’ conceptual understanding as well as the development of their attitudes and skills. A quantitative correlational design was employed. The analysis results indicate that the simultaneous implementation of the Love-Based Curriculum and deep learning approach has a significant relationship with learning outcomes, as evidenced by a Sig. F Change value of 0.002 and a contribution of 37.4% to the variation in student learning outcomes. The Love-Based Curriculum plays a role in creating a safe and comfortable learning environment, fostering empathy, care, and compassion among students, while the deep learning approach promotes the development of deep conceptual understanding through meaningful, reflective, and engaging learning. These findings suggest that integrating both approaches not only contributes to academic achievement but also supports the holistic development of students’ attitudes and skills.